Spontaneous Formation of Prebiotic Compartment Colonies on Hadean Earth and Pre‐Noachian Mars. Issue 3 (22nd April 2022) - Köksal, Elif S.; Põldsalu, Inga; Friis, Henrik; Mojzsis, Stephen J.; Bizzarro, Martin; Gözen, Irep
Abstract: The front cover artwork is provided by İrep Gözen group at the University of Oslo. The image shows primitive cell‐like compartments which have spontaneously emerged from a crack in rock‐forming mineral oligoclase. Read the full text of the Article at 10.1002/syst.202100040 . Abstract : "Our findings show how the first primitive cells might have developed on the early Earth with the support of solid surfaces…" This and more about the story behind the front cover can be found in the Article at 10.1002/syst.202100040 .